Peran Media Sosial Sebagai Platform Bisnis Digital Dalam Meningkatkan Penjualan Produk Lokal - Didin Muhidin; Robi Sunggara; Mus Mulyadi (Jurnal Ilmu Bisnis Digital, 2026)
The development of digital technology has encouraged changes in marketing strategies implemented by business actors, particularly through the utilization of social media as a digital business platform. This study aims to analyze the role of social media in increasing local product sales. The research employed a quantitative approach using a survey method involving 100 business owners who utilize social media for marketing purposes. Data were collected through questionnaires based on a Likert scale and analyzed using descriptive statistics and simple linear regression with SPSS software. The results indicate that social media has a positive and significant effect on increasing local product sales. Content quality, customer interaction, promotional frequency, and audience reach are the main factors supporting the effectiveness of social media marketing. Furthermore, social media helps businesses expand market reach, increase brand awareness, build consumer trust, and foster customer loyalty. The findings confirm that the optimal use of social media can serve as an effective strategy to support the growth and competitiveness of local products in the digital economy era. Therefore, business actors should develop more innovative and sustainable digital marketing strategies to maximize the potential of social media in improving business performance.